2022
DOI: 10.1590/fst.55120
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of apple phloretin on physiological and morphological properties of Listeria monocytogenes

Abstract: Green bactericides are excellent strategies for reducing food spoilage. Phloretin was regarded as efficient, broad-spectrum and safe preservative, which showed enormous potential in food industry. Inhibitory mechanism of phloretin on Listeria monocytogenes was systematically elucidated through integrity of cell membrane, intracellular protein content, energy level, and nucleic acid morphological character. SEM and TEM results showed minimal injury of cell membrane, which was further proved by a leakage of pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Similar decreases of the intracellular ATP content were observed in V. parahaemolyticus cells treated with lactobionic acid and eucalyptus essential oil. , Moreover, some studies revealed that natural antimicrobials caused the reduction of intracellular ATP levels by destructing cytoplasmic membranes. Based on this, it can be speculated that the hexanal may destroy the cell membrane of V. parahaemolyticus.…”
Section: Resultsmentioning
confidence: 59%
“…Similar decreases of the intracellular ATP content were observed in V. parahaemolyticus cells treated with lactobionic acid and eucalyptus essential oil. , Moreover, some studies revealed that natural antimicrobials caused the reduction of intracellular ATP levels by destructing cytoplasmic membranes. Based on this, it can be speculated that the hexanal may destroy the cell membrane of V. parahaemolyticus.…”
Section: Resultsmentioning
confidence: 59%
“…Phloretin is a member of the flavonoid class dihydrochalcones and is distributed mainly in green apples and strawberries ( Figure 1 ) [ 15 ]. The compound has antioxidant, anti-inflammatory [ 16 , 17 ], antidiabetic [ 18 , 19 ], anticancer, and antimicrobial properties [ 20 ]. However, phloretin’s poor water solubility reduces its absorption and, consequently, bioavailability, limiting its application in the treatment of various diseases and administration via conventional drug delivery systems [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In food science, the research of food sterilization is important to inactivate pathogenic microorganisms in foods and ensure food safety. Food spoilage and food poisoning often occur because of insufficient sterilization intensity (Sadiq et al, 2018;Zhao et al, 2022). More than 70% of food poisoning cases are caused by microorganisms, especially sporogenous bacteria (Ishaq et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most widely used method of spores inactivation in the industry is mainly heat treatment, but PATS can effectively inactivate spores at lower temperatures and in a shorter treatment time than heat treatment alone (Gomes et al, 2022;Luong et al, 2020;Ribeiro & Cristianini, 2020). PATS sterilization technology has lower heat treatment intensity than traditional thermal sterilization technology and can produce higher quality food (Deng et al, 2022;Sevenich et al, 2016). To further reduce the temperature used to inactivate the spores and reduce the impact on the sensory and nutritional values of the food, a combination of PATS combining with ε-polylysine (PL) was used to inactivate the spores.…”
Section: Introductionmentioning
confidence: 99%